Foodomics: A Data-Driven Approach to Revolutionize Nutrition and Sustainable Diets - Ahmed, Selena; de la Parra, John; Elouafi, Ismahane; German, Bruce; Jarvis, Andy; Lal, Vincent; Lartey, Anna; Longvah, T.; Malpica, Carlos; Vázquez-Manjarrez, Natalia; Prenni, Jessica; Aguilar-Salinas, Carlos A.; et al. (Frontiers in Nutrition, 2022)
Globally, we are failing to meet numerous nutritional, health, and environmental targets linked to food. Defining food composition in its full chemical and quantitative diversity is central to data-driven decision making for supporting nutrition and sustainable diets. ‘Foodomics,’ or the application of omics-technology to improve wellbeing, has the potential to comprehensively elucidate what is in food, how this composition varies with environmental, management, and processing factors across the food system, and importantly, how diet composition as an ensemble of foods guides outcomes for nutrition, health, and sustainability. Here, we outline: (1) challenges of evaluating food composition; (2) state-of-the-art omics technology and innovations for the analysis of food; and (3) application of foodomics to revolutionize nutrition and sustainable diets. Featuring efforts of the Periodic Table of Food Initiative, a participatory effort to create a globally shared foodomics platform, we conclude with recommendations to accelerate the field in ways that strengthen the capacity of scientists globally and benefit all people, particularly those most vulnerable to malnutrition and diet-driven illness.